2012
DOI: 10.1039/c2cs35014a
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic-like chemistry on Titan

Abstract: Titan, the largest satellite of Saturn, is the only one in the solar system with a dense atmosphere. Mainly composed of dinitrogen with several % of methane, this atmosphere experiences complex organic processes, both in the gas and aerosol phases, which are of prebiotic interest and within an environment of astrobiological interest. This tutorial review presents the different approaches which can be followed to study such an exotic place and its chemistry: observation, theoretical modeling and experimental si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 66 publications
0
60
1
Order By: Relevance
“…Organic growth processes through negative ion chemistry was also investigated between CN − ions and HC 3 N molecules (Žabka et al 2012). The first aim of these laboratory experiments is to address the question of how atmospheric chemistry can sustain the formation of complex organic matter and possibly prebiotic buildings blocks in a planetary system (Raulin et al 2012). This laboratory approach Fig.…”
Section: Simulation Facilities For Organic Aerosols In Planetary Atmomentioning
confidence: 99%
“…Organic growth processes through negative ion chemistry was also investigated between CN − ions and HC 3 N molecules (Žabka et al 2012). The first aim of these laboratory experiments is to address the question of how atmospheric chemistry can sustain the formation of complex organic matter and possibly prebiotic buildings blocks in a planetary system (Raulin et al 2012). This laboratory approach Fig.…”
Section: Simulation Facilities For Organic Aerosols In Planetary Atmomentioning
confidence: 99%
“…For example, these materials have been proposed to be the source of the distinctive orange, redbrown and black colors of comets and the atmosphere of planets and moons such as Saturn, Jupiter and Titan and carbonaceous meteorites, indicating their abundance in our solar system and the universe, respectively. 10,[14][15][16] However, the focus of prebiotic chemistry has always been on understanding the chemical origin of life and thus has remained highly fundamental research. 4 The application of prebiotic chemistry and specifically prebiotic polymers to material science has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent laboratory studies showed that when these tholins come into contact with oxygen-bearing molecules such as water (surface/subsurface ice on Titan), result in the formation of complex prebiotic molecules such as amino acids 5 and nucleobases 23,24 . Thus, atmospheric aerosol photochemistry has a key role in the processes leading to the potential prebiotic chemistry on Titan's surface 25 .…”
mentioning
confidence: 99%